A Study on the Opinions of Physiotherapists Regarding the Methods Used in the Recovery Process of Volleyball Players in the Libyan Premier League - Allafi, Alfetouri; Boukari , Samia; Mhenni, Thouraya; Attia , Ahmed; Sioud, Rime; Salameh, Hamed; Oueslati, Khouloud; Khalifa, Riadh (Advances in Social Sciences Research Journal, 2025)
This research aims to study the opinions of a group of Libyan physiotherapists about the recovery methods used in the recovery process of volleyball players in the Libyan Premier League. To achieve the research objective, the descriptive method was used as it suits the nature of this research. The sample consisted of 18 physical therapists who accompany volleyball players in sports clubs in Libya. The participants was selected intentionally. The research tools used in this study is the questionnaire. The most important results of this research are that the recovery methods used in the recovery process of volleyball players in the Libyan Premier League are cold water immersion, relaxation exercises, and massage. The order of the recovery methods used in the recovery process for volleyball players in the Libyan Premier League was as follows: first; cold water immersion, second; relaxation exercises, and third; massage. The most important recommendations of this study are to provide the necessary financial support for the use of modern devices and methods during the recovery process of volleyball players in Libya. We also recommend conducting similar research to determine the effectiveness of physical therapy programs in the recovery process for volleyball players in Libya.